2004
DOI: 10.1016/j.devcel.2004.10.002
|View full text |Cite
|
Sign up to set email alerts
|

ACAP1 Promotes Endocytic Recycling by Recognizing Recycling Sorting Signals

Abstract: Cargo sorting that promotes the transport of cargo proteins from a membrane compartment has been predicted to be unlikely in the endocytic recycling pathways. We now show that ACAP1 binds specifically and directly to recycling cargo proteins. Reducing this interaction for TfR inhibits its recycling. Moreover, ACAP1 binds to two distinct phenylalanine-based sequences in the cytoplasmic domain of TfR that function as recycling sorting signals to promote its transport from the recycling endosome. Taken together, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
125
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(137 citation statements)
references
References 21 publications
11
125
1
Order By: Relevance
“…How imatinib facilitates TfR1-Hsc70 interaction and trafficking to the lysosome for degradation is unclear. Perhaps most relevant is the well documented identification of two distinct phenylalanine-based sequences in the cytoplasmic TfR1 tail that recruits the ARF6 GTPase-activating protein called ACAP1 (39). Importantly, this interaction appears to promote cargo sorting of GLUT4 as well as both TfR1 and the integrin receptors (6).…”
Section: Discussionmentioning
confidence: 99%
“…How imatinib facilitates TfR1-Hsc70 interaction and trafficking to the lysosome for degradation is unclear. Perhaps most relevant is the well documented identification of two distinct phenylalanine-based sequences in the cytoplasmic TfR1 tail that recruits the ARF6 GTPase-activating protein called ACAP1 (39). Importantly, this interaction appears to promote cargo sorting of GLUT4 as well as both TfR1 and the integrin receptors (6).…”
Section: Discussionmentioning
confidence: 99%
“…Rab/Arf cross-talk is likely important for many higherlevel processes that depend upon tight regulation of recycling endosome function. Previous studies in mammals demonstrated a role for ACAP1 in Glut4 and integrin recycling (39,40). Furthermore, ACAP1 was reported to be part of a clathrin-coat complex on endosomes (31).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse anti-GFP and rabbit anti-GAPDH antibodies were obtained from Covance. Alexa Fluor 488-conjugated Tf has been described (27).…”
Section: Methodsmentioning
confidence: 99%
“…Equilibrium centrifugation using sucrose gradients was performed essentially as described (14), except total cell homogenate rather than Golgi-enriched fraction was loaded at the bottom of the gradient for floatation analysis. TfR internalization assay was performed as described (27).…”
Section: Methodsmentioning
confidence: 99%